Lesly got 14 answers correctly.
- Let the correct answers be C.
- Let the incorrect answers be I.
<u>Given the following data:</u>
- Total number of questions = 30 questions.
To find the number of answers she got correctly;
× ![30](https://tex.z-dn.net/?f=30)
× ![2](https://tex.z-dn.net/?f=2)
<em>Correct answers, C </em><em>= </em><em>14 answers</em>
Therefore, Lesly got 14 answers correctly.
Read more: brainly.com/question/24613908
Answer:
False
True
False
False
Step-by-step explanation:
1. We have to get the sum as follows :
![3\frac{4}{9} + 4\frac{6}{9}](https://tex.z-dn.net/?f=3%5Cfrac%7B4%7D%7B9%7D%20%2B%204%5Cfrac%7B6%7D%7B9%7D)
= ![\frac{31}{9} + \frac{42}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B31%7D%7B9%7D%20%2B%20%5Cfrac%7B42%7D%7B9%7D)
= ![\frac{31 + 42}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B31%20%2B%2042%7D%7B9%7D)
= ![\frac{73}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B73%7D%7B9%7D)
= ![8\frac{1}{9} \neq 7\frac{1}{9}](https://tex.z-dn.net/?f=8%5Cfrac%7B1%7D%7B9%7D%20%5Cneq%20%207%5Cfrac%7B1%7D%7B9%7D)
So, this is false.
2. We have to get the sum as follows :
![4\frac{5}{6} + 1\frac{3}{6}](https://tex.z-dn.net/?f=4%5Cfrac%7B5%7D%7B6%7D%20%2B%201%5Cfrac%7B3%7D%7B6%7D)
= ![\frac{29}{6} + \frac{9}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B29%7D%7B6%7D%20%2B%20%5Cfrac%7B9%7D%7B6%7D)
= ![\frac{29 + 9}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B29%20%2B%209%7D%7B6%7D)
= ![\frac{38}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B38%7D%7B6%7D)
= ![6\frac{2}{6}](https://tex.z-dn.net/?f=6%5Cfrac%7B2%7D%7B6%7D)
So, this is true.
3. We have to get the difference as follows :
![4\frac{5}{8} - 2\frac{4}{8}](https://tex.z-dn.net/?f=4%5Cfrac%7B5%7D%7B8%7D%20-%202%5Cfrac%7B4%7D%7B8%7D)
= ![\frac{37}{8} - \frac{20}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B37%7D%7B8%7D%20-%20%5Cfrac%7B20%7D%7B8%7D)
= ![\frac{37 - 20}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B37%20-%2020%7D%7B8%7D)
= ![\frac{17}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B17%7D%7B8%7D)
= ![2\frac{1}{8} \neq 2\frac{3}{8}](https://tex.z-dn.net/?f=2%5Cfrac%7B1%7D%7B8%7D%20%5Cneq%20%202%5Cfrac%7B3%7D%7B8%7D)
So, this is false.
4. We have to get the difference as follows :
![7\frac{5}{8} - 4\frac{2}{8}](https://tex.z-dn.net/?f=7%5Cfrac%7B5%7D%7B8%7D%20-%204%5Cfrac%7B2%7D%7B8%7D)
= ![\frac{61}{8} - \frac{34}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B61%7D%7B8%7D%20-%20%5Cfrac%7B34%7D%7B8%7D)
= ![\frac{61 - 34}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B61%20-%2034%7D%7B8%7D)
= ![\frac{27}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B27%7D%7B8%7D)
= ![3\frac{3}{8} \neq 3](https://tex.z-dn.net/?f=3%5Cfrac%7B3%7D%7B8%7D%20%5Cneq%20%20%203)
So, this is also false. (Answer)
Since you’re multiplying n^-6 and n^3, you can add the exponents: -6+3 = -3
n^-6 * n^3 = n^-3
If you need to finish without having a negative exponent in your answer, then remember a negative exponent means that factor is on the wrong side of the fraction.
n^-3 = n^-3 / 1 = 1/n^3
when the factor moves to the other side of the fraction, the side of the exponent changes.
Ella is 13 years, four months, and 19 days old.